KEBIJAKAN INDONESIA BELUM MENGAKUI KEMERDEKAAN KOSOVO PADA TAHUN 2008 - Mauliani, Ressy; Pakpahan, Saiman (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Sosial dan Ilmu Politik, 2016)
The purpose of this research is to understand Indonesia Foreign Policy Has Not Admitted Kosovo Independence In 2008. Kosovo is a province in Serbia, but due to the uprising finally Kosovo secede from Serbia and stands today as a nation that also require confessions from other countries. Most countries chose to recognized and ignore the Kosovo Independence. Differently, Indonesia chose to did not recognize Kosovo Independence in 2008. Thus researcher question is Why Indonesia Foreign Policy Has Not Admitted Kosovo Independence In 2008.This research theoretically has built with Realism perspectives on International Relations and supported by Foreign Politic theory James N. Rossenau. Formulation of all arguments, facts, and theoretical framework on this research is guided by qualitative explanation methods. Technique in this research is through by the study of library. Data which is gotten and collected through the journal books, the last thesis and then from internet has related to the problems.Researcher has formulated answered-hypothesis whic reveals the fact that Indonesia actually put themselve in the position of "wait and see" to the development of the newly established state. On the basis of the existing separatist movements in Indonesia could trigger a conflict that can lead to the release of such regions of Indonesia and East Timor. For that, in taking the decision to admit other countries, Indonesia is very cautious dala take a decision as this will have a direct impact for IndonesiaKeywords : Foreign Policy, Indonesia, Kosovo, Independence, Separatism, Recognize